P072 Safety analysis of vedolizumab during pregnancy: Findings from a reproductive study in monkeys. (16th January 2018) - Crawford, D; Friedman, M
Abstract: Background: Vedolizumab (VDZ) is a gut-selective humanised monoclonal antibody targeting α4 β7 integrin, approved for adults with moderate-to-severe ulcerative colitis and Crohn's disease. The few publications reporting on VDZ use in pregnancy have not identified any incidence of maternal or foetal toxicity. The objective of this study was to evaluate the effects of VDZ on pregnancy, parturition and lactation in cynomolgus monkeys and on survival, growth and postnatal development of the offspring. Methods: Non-fasted pregnant cynomolgus monkeys were randomly assigned to receive 0 mg/kg (saline control), 10 mg/kg (human equivalent dose [HED]: 3.2 mg/kg) or 100 mg/kg (HED: 32.3 mg/kg) of VDZ ( n = 12/group) every 2 weeks (total of nine intravenous infusions between gestational Days [GD] 20 and 140). Dams and infants were monitored for clinical signs, development, neurobehaviour and grip strength, then euthanised at 181 ± 1 days postpartum. Levels of VDZ and primate anti-human antibody (PAHA) were assessed by direct enzyme-linked immunosorbent assay (ELISA) in the serum at GD 20 and 132 and in the breast milk at 28 ± 1 days postpartum of the dams, and in the serum of the infants at postpartum Days 20 and 120. Results: The number of pregnant females was similar across the three groups. There were no VDZ-related maternal deaths and no increase in the incidence of prenatal loss or stillbirth in any group. No VDZ-related effects on the number of infants born, clinical signs or infant development were noted. In the dams at GD 132, time to the maximum serum concentration of VDZ after administration was 3.4 ± 6.7 h in the 100 mg/kg group (Table 1). At necropsy, no VDZ-related maternal organ toxicity was found. Low levels of VDZ (0.16–0.27 μg/ml) were found in the breast milk of 3/11 monkeys in the 100 mg/kg group. No VDZ-related effects were found on grip strength, neurobehavioural or morphological assessments in the infants. In the 10 and 100 mg/kg groups, positive PAHA titres were detected in 9/12 dams (each group), and 2/7 and 1/9 infants, respectively. Neutralising effects on VDZ toxicokinetics and pharmacodynamics were strongest in pregnant monkeys dosed at 10 mg/kg. Conclusions: Administration of VDZ to pregnant monkeys resulted in no evidence of effects on teratogenicity, prenatal or postnatal neurobehavioural and overall development in infants up to 6 months of age. At the no-observed-adverse-effect-level of 100 mg/kg, the serum exposure was 346 times higher in monkeys than in humans dosed at VDZ 300 mg.